Joko Widodo's Speech at the ASEAN Business and Investment Summit 2021 in the Representation of Power and Ideology - Haryo Sutanto (Communicare : Journal of Communication Studies, 2022)
A speech reflects the power and ideology of the communicator when it is delivered. It also has the representation of the social and political situation at the time it is delivered. President Joko Widodo delivered his speech at the Association of Southeast Asian Nations (ASEAN) Business and Investment Summit (ABIS) on October 25, 2021. The speech is about the successful handling of the Covid-19 Pandemic and the initial success of economic recovery among ASEAN countries. Indonesia would have the ASEAN Chair in 2023 and it means Indonesia would lead ASEAN in a new digital era and new normal era that is accelerated by the Covid-19 pandemic. The power and ideology of President Joko Widodo's speech reflect the leadership charm of Indonesia throughout the ASEAN Chair in 2023. The reflection is exposed through the power and ideology of Indonesia and President Joko Widodo that embraces all southeast Asia countries in ASEAN to develop together in handling the Covid-19 pandemic and recovering the ASEAN economy under Indonesia's leadership in ASEAN Chair 2023.